Molecular Study of spy1258 and smeZ genes in Group A Streptococcal Tonsillitis - Zainab Dakhil Degaim; Esraa Dhaher Taher; Mohammed Jasim M. Shallal (Journal of Pure and Applied Microbiology, 2019)
Streptococcus pyogenes was the most common bacterial causes of tonsillitis. The detection of virulence factors of this pathogen can be used to determine pathogenic potential as a rapid screening method. A total of 109 isolates (46%) showed positive culture for S. pyogenes, these isolates recovered from 235 swabs were collected from tonsillitis patients in ENT department in Al–Habboby Teaching Hospital, Thi-Qar province, Iraq. S. pyogenes isolates exposed to detect the specific gene (spy1258)and one of the virulence factors were smeZ gene by PCR technique and DNA sequencing analysis. The PCR results recorded that 61% and 50% of isolates harbor spy1258 and smeZ genes, respectively. The sequencing of PCR products showed significant alignments identities (94-100%) to the S. pyogenes for both genes which are located in BLAST-NCBI Genbank. The four PCR products of both genes were registered in Genbank under the named as (ZKD1 Spy-like gene; ZKD2 Spy-like gene; ZKD3 SmeZ-like gene and ZKD4 SmeZ-like gene). The results of Multiple sequence alignment analysis recorded that C > T and T > C polymorphism for smeZ gene.